The Influence of Competence and Compensation on Employee Job Satisfaction at the Corporate and Foreign Tax Service Office (KPP Badora) with Work Motivation as an Intervening Variable - Cahyo Ertanto (Journal of Islamic Studies & Social Science, 2024)
The purpose of this study was to determine the effect of competence and compensation on employee job satisfaction with work motivation as an intervening variable. The research method used is the explanatory analysis approach. This means that each variable presented in the hypothesis will be observed through testing the causal relationship of the independent variable to the dependent variable. The population in this study amounted to 129 people with a sample of 104 employees of the Pratama Tax Service Office (KPP) for Corporate and Foreigners. The data collection technique used was primary and secondary data. The data analysis method in this study includes instrument testing, assumption testing, model testing, and hypothesis testing to ensure that the data used meets the required criteria and provides valid results.The results of the study showed that 1) based on the results of the competency test, it has a significant effect on work motivation. 2) Based on the results of the compensation test, it has a significant effect on work motivation. 3) Based on the results of the competency test, it has an effect on job satisfaction. 4) Based on the results of the compensation test, it has an effect on job satisfaction. 5) Based on the test results, work motivation has an effect on job satisfaction. 6) Based on the test results, the indirect effect has a smaller value than the direct effect.